Measuring The Performance of Islamic Banks Using The Shidiq Amanah Tabligh and Fathona Models - Andi Muhammad Rizal; Aedy , Hasan; Ma’mun , Siti Zakiah (Perisai : Islamic Banking and Finance Journal, 2024)
The difference in the operational system principles of Islamic banks and conventional banks should have an impact on the difference in bank performance assessments. This study aims to evaluate the performance of the financial aspects, social aspects, and sharia compliance aspects of Islamic banks (SATF value). The type of research is quantitative descriptive using secondary data. The research population is Islamic banks operating in Indonesia for the period 2021-2022. The sampling technique used purposive sampling with three selected banks: Bank Syariah Indonesia (BSI), Bank Muamalat Indonesia (BMI), and Bank Mega Syariah (BMS). The data uses are annual reports and corporate governance reports from the official websites of Islamic banks. The data analysis technique uses simple additive weighting (SAW). The results of the study generally show that the SATF value performance that focuses on the social perspective has a low concern for social aspects. This study can be a reference for future research and can provide valuable guidance for maintaining and improving the performance of Islamic banks, while actively correcting any weaknesses or deficiencies identified.